2020
DOI: 10.1088/1742-6596/1469/1/012171
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Process Oriented Guided Inquiry Learning (POGIL) on mathematical problem solving abilities

Abstract: This research aimed to identify the effect of POGIL model on the students’ mathematical problem-solving ability. The variables involved in this research were mathematical problem-solving abilities as an independent variable, and the POGIL model as a dependent variable. Based on the observations of researchers through interviews with mathematics subject teachers and students at Junior High School 2 Kalibagor, showed that the mathematical learning process that took place was still dominated by learning that did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…Theoretically, the POGIL model more directed the students to easily understand the learning material (Bénéteau et al, 2017;Bressette, 2008;Hu & Shepherd, 2014;Kim, 2018;Kussmaul et al, 2016;Muhammad & Purwanto, 2020;Rumain & Geliebter, 2020;Straumanis & Simons, 2008;Williamson et al, 2013) and the students could solve the problems given by the teacher through a teamwork (Eberlein et al, 2008;Kussmaul, 2012;Muhammad & Purwanto, 2020). A teamwork learning would make the students to more develop their thinking skill in the higher level (Muhammad & Purwanto, 2020;Rustam, Ramdani, & Sedijani, 2017), it was due to the students' roles that were more active and it made the learning processes more interesting (Kussmaul, 2014). Additionally, the learning using a POGIL model would actively motivate the students to get their knowledge (Yadav et al, 2019;Yuliastini et al, 2018); subsequently, the students became an independent person, skilled, had scientific abilities, and active in solving the problems based on the knowledge gained (Hu & Kussmaul, 2012;Natalina et al, 2013;Vincent-Ruz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, the POGIL model more directed the students to easily understand the learning material (Bénéteau et al, 2017;Bressette, 2008;Hu & Shepherd, 2014;Kim, 2018;Kussmaul et al, 2016;Muhammad & Purwanto, 2020;Rumain & Geliebter, 2020;Straumanis & Simons, 2008;Williamson et al, 2013) and the students could solve the problems given by the teacher through a teamwork (Eberlein et al, 2008;Kussmaul, 2012;Muhammad & Purwanto, 2020). A teamwork learning would make the students to more develop their thinking skill in the higher level (Muhammad & Purwanto, 2020;Rustam, Ramdani, & Sedijani, 2017), it was due to the students' roles that were more active and it made the learning processes more interesting (Kussmaul, 2014). Additionally, the learning using a POGIL model would actively motivate the students to get their knowledge (Yadav et al, 2019;Yuliastini et al, 2018); subsequently, the students became an independent person, skilled, had scientific abilities, and active in solving the problems based on the knowledge gained (Hu & Kussmaul, 2012;Natalina et al, 2013;Vincent-Ruz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reveal statistically significant differences in critical thinking skills and problemsolving skills in favour of the POGIL group compared to the lecture group of university chemistry students (Irwanto et al, 2018). Learners taught using POGIL had a better mathematical problem-solving ability (Muhammad & Purwanto, 2020) and improved logical thinking ability in solving mathematical problems as compared to the learners taught using conventional learning methods (Andriani et al, 2019). Carefully structured and systematically implemented POGIL intervention helped Grade 10 science learners improve their perceptions of chemistry learning (Treagust et al, 2020).…”
Section: / 11mentioning
confidence: 97%
“…Douglas & Chiu, (2013) conclude that theoretically the process oriented guided inquiry learning (PO-GIL) learning model has a positive effect on science process skills (KPS) and students' cognitive abilities. Muhammad & Purwanto, (2020) also stated that the POGIL model can improve critical thinking skills and improve aspects of hypothesizing, analyzing and concluding. From the various research results that have been carried out above, it can be concluded that the PO-GIL learning model provides positive results on understanding science concepts, science process skills, and critical thinking skills.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 presents the learning model with POGIL proposed by (Muhammad & Purwanto, 2020). The POGIL learning cycle begins with an exploration of a 'model'.…”
Section: Introductionmentioning
confidence: 99%